Children's stress regulation mediates the association between prenatal maternal mood and child executive functions for boys, but not girls. (2nd August 2018) - Neuenschwander, Regula; Hookenson, Kaia; Brain, Ursula; Grunau, Ruth E.; Devlin, Angela M.; Weinberg, Joanne; Diamond, Adele; Oberlander, Tim F.
Abstract: Prenatal exposure to maternal mood disturbances shapes children's cognitive development reflected in the critical construct of executive functions (EFs). Little is known, however, about underlying mechanisms. By examining cortisol responses in both everyday and lab challenge settings, we tested whether the child/offspring hypothalamic–pituitary–adrenal axis mediates effects of prenatal maternal mood on child EFs at age 6. In 107 Canadian children born to women with a wide range of anxious and depressive symptoms during pregnancy, we found that in boys but not girls, depressed and/or anxious prenatal maternal mood is associated with heightened diurnal cortisol levels in everyday settings, as well as heightened cortisol reactivity to a lab challenge and that this heightened reactivity was associated with poorer EFs. Among boys we also observed that cortisol reactivity but not diurnal cortisol mediated the association between depressed and/or anxious prenatal maternal mood and EFs. Depressed and/or anxious prenatal maternal mood was related to child EFs for both girls and boys. To our knowledge, this is the first study to demonstrate a mediating role for child stress regulation in the association between prenatal maternal stress-related mood disturbances and child EFs, providing evidence of a mechanism contributing to fetal programming of cognition.